2009
DOI: 10.3109/03009740903002257
|View full text |Cite
|
Sign up to set email alerts
|

Small bone lesions resembling erosions can frequently be found in bilateral wrist MRI of healthy individuals

Abstract: A few small bone lesions that could potentially be confused as erosions were detected in about half of the normal volunteers. These findings should always be evaluated with reference to the clinical picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
3
19
1
1
Order By: Relevance
“…These criteria are based on 4 main domains: joint involvement (detected by clinical examination, ultrasonography, or MRI), serology (anti-CCP and RF), acute-phase reactants (CRP level and erythrocyte sedimentation rate), and duration of synovitis. The findings of the present study, in which we demonstrated that changes revealed on MRI of the joints of healthy subjects resembled pathologic features of the RA joint, are in accordance with the results from other MRI studies of healthy subjects (18,19), and thus these findings underscore the need for establishment of a threshold to indicate which types and grades of MRI findings should be used to designate a "positive" result on MRI. Our study was planned, powered, and designed with the ACR 1987 criteria for RA as the standard reference.…”
Section: Discussionsupporting
confidence: 91%
“…These criteria are based on 4 main domains: joint involvement (detected by clinical examination, ultrasonography, or MRI), serology (anti-CCP and RF), acute-phase reactants (CRP level and erythrocyte sedimentation rate), and duration of synovitis. The findings of the present study, in which we demonstrated that changes revealed on MRI of the joints of healthy subjects resembled pathologic features of the RA joint, are in accordance with the results from other MRI studies of healthy subjects (18,19), and thus these findings underscore the need for establishment of a threshold to indicate which types and grades of MRI findings should be used to designate a "positive" result on MRI. Our study was planned, powered, and designed with the ACR 1987 criteria for RA as the standard reference.…”
Section: Discussionsupporting
confidence: 91%
“…The authors diagnosed up to two small bone lesions resembling erosions in nearly half of the subjects. All lesions were small, the numbers increased with age and were most commonly located on the volar aspect of the lunate, scaphoid, trapezium/trapezoid, triquetrum and the capitate of the dominant hand 13. Except for the side preference which could not be accurately assessed in our study due to the small number of left-handed children, their findings support ours although the MRI machine and technique used differed between the two studies.…”
Section: Discussionsupporting
confidence: 81%
“…This contrasts the results of a Finnish study [11] including 31 healthy adults (32-46 years old), where only one suspected erosion was seen radiographically, and only 50% had MRI changes that could be mistaken for erosive change as defined in the OMERACT recommendations [5,6]. Some of the differences may be due to different perception of what to call a "bony depression" since there is no objective definition of an erosion radiographically or on MRI in children.…”
Section: Discussioncontrasting
confidence: 76%
“…During the last decade, extensive work has been carried out to describe and standardise definitions of radiological key abnormalities, establish scoring systems for disease activity and degree [5,7], and validate imaging techniques and protocols [8][9][10]. Interestingly, little attention has been given to normal variations that resemble disease, such as cortical irregularities and pits [11]. This is of particular importance in the growing paediatric skeleton.…”
Section: Introductionmentioning
confidence: 99%